2020
DOI: 10.1542/peds.2020-0557
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten Readiness in Children Who Are Deaf or Hard of Hearing Who Received Early Intervention

Abstract: BACKGROUND: Children who are deaf or hard of hearing (D/HH) have improved language outcomes when enrolled in early intervention (EI) before the age of 6 months. Little is understood about the long-term impact of EI on outcomes of kindergarten readiness (K-readiness). The study objective was to evaluate the impact of EI before the age of 6 months (early) versus after 6 months (later) on K-readiness in children who are D/HH. METHODS: In this study, we leveraged data from the Ohio Early Hearing Detection and Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For infants and toddlers who are DHH, EI plays a prominent role by providing services that support language and other skills important for growth and development. Research has historically focused on outcomes associated with age of EI enrollment; earlier exposure to EI is associated with better outcomes in both the short-term (language and vocabulary) [ 8 , 9 , 10 , 11 ] and longer-term (early academic outcomes) [ 16 , 33 ]. However, few reported studies have evaluated intensity measures in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For infants and toddlers who are DHH, EI plays a prominent role by providing services that support language and other skills important for growth and development. Research has historically focused on outcomes associated with age of EI enrollment; earlier exposure to EI is associated with better outcomes in both the short-term (language and vocabulary) [ 8 , 9 , 10 , 11 ] and longer-term (early academic outcomes) [ 16 , 33 ]. However, few reported studies have evaluated intensity measures in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the Ohio Data Linkage Project, describing the linkage methodology and data for the present study, has been published previously [ 15 , 16 ] and is summarized briefly here. The Ohio Data Linkage Project was a multi-agency collaboration that successfully linked data from two state-level public health databases to better understand outcomes in children who are DHH born between 2008 and 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The U.S. National Institutes of Health Consensus Development Conference (1993) released a consensus statement recommending implementation of UNHS for all children by 3 months of age.The availability of UNHS allowed for the Joint Committee on Infant Hearing of the American Academy of Pediatrics (2007) to establish the “1-3-6” guideline: that children undergo hearing screening by 1 month of age, complete diagnostic assessment by 3 months of age if needed, and receive early intervention by 6 months of age if they have hearing loss ( Meinzen-Derr et al.,2020 ). For a child with congenital deafness, hearing amplification will not provide benefit; therefore, intervention requires adoption of sign language, cochlear implantation, or often a combination of both.…”
Section: The Role Of Universal Newborn Hearing Screeningmentioning
confidence: 99%
“…Only about half of the teenagers with cochlear implants attain an age-appropriate level of reading comprehension [ 21 ]. In contrast to risk for academic underachievement later in life, a recent study on 385 pre-schoolers with HL showed that those who started receiving early intervention by the age of 6 months had similar rates of kindergarten readiness to the total population of kindergarteners [ 22 ]. A substantial number of studies report cognitive delays in children with HL, particularly elevated risks for delays in social cognition [ 23 , 24 ] and executive functioning [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%